Public transit reorganization policies in the Metropolitan Area of Lima during the coronavirus pandemic Covid-19 - Poole Fuller , Esteban (2021)
Lima is currently home to nearly half of the people infected by the Sars-cov-2 coronavirus (Covid-19). Within this metropolitan area, public transportation is one of the main spreading sources of the virus. In this context, the Peruvian government has sought to establish greater regulation of public transport to mitigate the factors that facilitate the spread of Covid-19. This article analyses these public interventions in the context of the tensions arising from the efforts to reorganize public transport in Lima and the obstacles posed by its high levels of informality. To this end, legal norms and public policy instruments are reviewed with attention to the analysis of the public transport subsidy scheme adopted in the context of the pandemic. It is concluded that public interventions in the face of the pandemic have been ineffective and evidence of the limited capacity of the State to guarantee compliance with sectoral regulations, as well as the scarce will to invest resources to promote the improvement of public transportation services